2005
DOI: 10.1016/j.chemgeo.2004.06.055
|View full text |Cite
|
Sign up to set email alerts
|

Supergene destruction of a hydrothermal replacement alunite deposit at Big Rock Candy Mountain, Utah: mineralogy, spectroscopic remote sensing, stable-isotope, and argon-age evidences

Abstract: Big Rock Candy Mountain is a prominent center of variegated altered volcanic rocks in west-central Utah. It consists of the eroded remnants of a hypogene alunite deposit that, at~21 Ma, replaced intermediate-composition lava flows. The alunite formed in steam-heated conditions above the upwelling limb of a convection cell that was one of at least six spaced at 3-to 4-km intervals around the margin of a monzonite stock. Big Rock Candy Mountain is horizontally zoned outward from an alunite core to respective kao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…The White Horse deposit was chosen for this study because of a relatively horizontal level of erosion across the deposit that has preserved a strong concentric "bulls-eye" alteration pattern centered on the replacement alunite. Data from this deposit complement recently published studies of a similar hydrothermal system at nearby Big Rock Candy Mountain (Rockwell, 2004;Cunningham et al, 2005;Rockwell et al, 2005) that has been eroded to deeper levels, providing excellent exposure of the vertical zonation through the system and insight into its natural destruction. Rockwell (2004) examined spectral variations in iron-bearing rocks and soils near the Trinity mine and Big Rock Candy Mountain that are related to variations in grain size and/or mineral abundance.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…The White Horse deposit was chosen for this study because of a relatively horizontal level of erosion across the deposit that has preserved a strong concentric "bulls-eye" alteration pattern centered on the replacement alunite. Data from this deposit complement recently published studies of a similar hydrothermal system at nearby Big Rock Candy Mountain (Rockwell, 2004;Cunningham et al, 2005;Rockwell et al, 2005) that has been eroded to deeper levels, providing excellent exposure of the vertical zonation through the system and insight into its natural destruction. Rockwell (2004) examined spectral variations in iron-bearing rocks and soils near the Trinity mine and Big Rock Candy Mountain that are related to variations in grain size and/or mineral abundance.…”
Section: Introductionsupporting
confidence: 61%
“…The tops of the upwelling limbs of these convective systems are marked by areas of intense advanced argillic alteration in fractured, permeable zones of volcanic rocks near the paleoground surface. Geochronologic studies have indicated that most of the hydrothermal systems and related alteration formed between 23 and 22 Ma (Cunningham et al, 1984) although Big Rock Candy Mountain is slightly younger (Cunningham et al, 2005). Figures 1 and 2 show the distribution of the replacement alunite deposits around the quartz monzonite intrusions.…”
Section: Geologic Setting and Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that ASTER visible, NIR, and SWIR data can be used to differentiate chlorite and epidote (as a group) from carbonates by exploiting the deep absorption caused by ferric/ferrous iron centered around 1.0 µm that is present in chlorite and epidote (and many mafi c minerals) but not in pure carbonates (Hewson et al, 2005). In other areas, propylitic calcite and epidote have been identifi ed using ASTER SWIR data (Rockwell et al, 2006), and are readily discernable with spectroscopic data such as AVIRIS (Airborne Visible/Infrared Imaging Spectrometer) (Rockwell et al, 2000Rowan and Mars, 2003;Cunningham et al, 2005), HyMap, or HyperSpecTIR, although intimate mixing of these minerals can cause diffi culties (Dalton et al, 2004). In Paleozoic carbonate rocks, the distribution of hydrothermal dolomite occurrences can be used to map fl ow paths of hot basinal brines that generate SEDEX (sedimentary exhalative) and MVT (Mississippi Valley type) deposits (e.g., Diehl et al, 2005).…”
Section: Remote Identifi Cation Of Quartz and Carbonate Minerals Nevadamentioning
confidence: 99%
“…Deep drilling cores for the study provides the most direct verifiable information, subject to analysis and testing for a long time, testing costs higher limit, unable to effectively carry out a large number of traditional geological analysis testing. In recent years, with the improvement of hyperspectral sensor accuracy and improved identification of high spectral mineralogical alteration extraction method using visible -near infrared reflectance spectroscopy, fast, economical and more accurate information to carry out geological core drilling research, information provided favorable metallogenic model for deep analysis and prospecting prediction [3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%